Ibn Daud's Critique of Ibn Gabirol’s definition of Prime Matter & Dominicus Gundissalinus’ Views - Eran, Amira (Anales del Seminario de Historia de la Filosofía, 2023)
Abraham Ibn Daud harshly criticizes the philosopher and the great poet Ibn Gabirol in his Exalted Faith. In this paper, I intend to prove that the genuine object of this critique is Dominicus Gundissalinus, Ibn Daud's partner in translating Avicenna’s Shifa’ from Arabic into Latin. In addition to their work as translators, Gundissalinus and Ibn Daud also wrote books of their own. In this paper, I discuss the definition of prime matter used by Avicenna and Ibn Gabirol and embraced by Ibn Daud and Gundissalinus. I bring textual proofs to show that in most of cases where Ibn Daud criticizes Ibn Gabirol, he is actually referring to the instances in which Gundissalinus abandons Avicenna's views and instead adopts Ibn Gabirol's standpoints.